Irradiation on Extramedullary Plasmacytoma of Vulva : A case report - Tirawan Sutedja; Nana Supriana; Angela Giselvania; Henry Kodrat (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2022)
Plasma cell neoplasm is a clonal plasma cell malignancy which is the result of B cell differentiation with special characteristics the presence of immunoglobulin secretion. The clinical presentation varies from monoclonal gammopathy to plasma cell leukemia. Only five to six percent of plasma cell neoplasms manifest as plasmacytoma.Solitary extramedullary plasmacytoma (EMP) in the vulva region is a rare case. The current study presents a recurrence case of EMP in left labia minora-vulva in 61-years-old patients who have undergone surgery with a complete response. Radiotherapy was given with a total dose of External Beam Radiotherapy (EBRT) 50.4 Gy and continued with brachytherapy cylinder intravagina five Gy in three fractions. Six months after complete radiation, there was no recurrence, metastasis or progression at follow-up.